Applying storytelling and gaming approach in multimedia application for preschool student / Mohammad Siddiq Rosely - Rosely, Mohammad Siddiq (Faculty of Computer and Mathematical Sciences, 2007)
The importance of information technology in education is not a new issue in this Information Communication Technology era. The usi^e of multimedia such as audio, video, animation and graphic make the teaching more interesting and Am. One of the ways of teaching is storytelling. This project is covering the concept of storytelling and gaming in developing the prototype of application that suitable for preschool student. The way of developing the application is based on the research that have been done before about the storytelling and the interface of the application that suitable for the certain audience. The storytelling is all about the preparation of student name Siti to school. The story begin with the moment she wakes up until the moment she is ready to go to school. There will be a game after the story end. Keyword: Storytelling, game, multimedia storytelling.